The effect of trunk massage on heart rate of female rowers in serial activities - Saeed Ghaeeni; Farid Mohammad Zadeh; Mehdi Abbaspoor; Faranak Amir Khani (Sport Sciences and Health Research)
The aim of this research was to determine the effect of trunk massage on heart rate of female rowers in serial activities. For this purpose, ten female (19.2±1.2 yrs) were sailing the 200 meters long lake, two sessions in 3 sets. At 15-minute rest intervals between series, they have used recovery with or without massage in each session. ANOVA Results showed that unlike to recovery without massage which has no effects on sets' heart rates, recovery with massage caused a significant reduction of before performance heart rate in 2th (84.8±3.3) and 3th series (84.5±6.8) relative to first set (92.2± 8.4) and after performance heart rate in 3th set (101.8±7.8) relative to 2th set (109.8±13.7). These findings can indicate that massage reduces heart rate in serial activities, although its volume and intensity should be varied due to the density of exercise pressures.